2020
DOI: 10.3389/fpsyt.2020.556759
|View full text |Cite
|
Sign up to set email alerts
|

Higher Body-Mass Index and Lower Gray Matter Volumes in First Episode of Psychosis

Abstract: Background Neurostructural alterations are often reported in first episode of psychosis (FEP), but there is heterogeneity in the direction and location of findings between individual studies. The reasons for this heterogeneity remain unknown. Obesity is disproportionately frequent already early in the course of psychosis and is associated with smaller brain volumes. Thus, we hypothesized that obesity may contribute to brain changes in FEP. Method We analyzed MRI scans f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…Despite the many links between obesity, schizophrenia and the brain, this remains an under researched area. We have previously demonstrated that in people with first episode of psychosis, obesity was associated with advanced brain age and lower cerebellar volume [ 23 , 24 ] and that BMI was a predictor of future neurostructural alterations [ 20 ]. The single previous study in 32 older individuals with schizophrenia found that higher BMI was significantly associated with lower volume of total gray matter, orbitofrontal and prefrontal cortices, and hippocampus [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the many links between obesity, schizophrenia and the brain, this remains an under researched area. We have previously demonstrated that in people with first episode of psychosis, obesity was associated with advanced brain age and lower cerebellar volume [ 23 , 24 ] and that BMI was a predictor of future neurostructural alterations [ 20 ]. The single previous study in 32 older individuals with schizophrenia found that higher BMI was significantly associated with lower volume of total gray matter, orbitofrontal and prefrontal cortices, and hippocampus [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, we do not know the temporal direction or pathophysiology of these findings. It is possible that overweight/obesity caused the observed changes through a range of mechanisms, including effects of adipokines [58], oxidative stress, systemic inflammation [59,60], insulin resistance/diabetes [16,27], hypertension [15,39] or dyslipidemia [60]. Smaller brain volumes in obesity may also reflect lower mobility/fitness or sedentary lifestyle, which are associated with the volumes of hippocampus [61] or motoric brain regions, including striatum [62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…We do not know the direction or pathophysiology of the association between lower cortical thickness and obesity. It is possible that overweight/obesity caused the observed changes through a range of mechanisms, including effects of adipokines, oxidative stress, systemic inflammation, insulin resistance/diabetes, 12,35 hypertension, atherosclerosis 36,37 or dyslipidemia, 38 but also lower mobility/fitness or sedentary lifestyle 39 . However, the reverse causality is also possible, where neurostructural alterations cause obesity, possibly through impulsivity, conditioning, or impaired homeostatic regulation.…”
Section: Discussionmentioning
confidence: 99%